Performance indicators for hospital services for older people - Challiner, Yvonne; Carpenter, G. Iain; Potter, Jonathan; Maxwell, Colleen (Age and ageing, 2003)
Background: standardised assessment is recommended in geriatric practice to improve patient care and generate quality data for audit and research. High level indicators used to measure performance of rehabilitation units suggested that more patients were discharged to long‐term residential care from one of two hospitals in a Health Authority in South East England. Objectives: to test whether the information provided by standardised assessment could inform performance indicators used to compare outcomes between hospitals. Design: prospective observational study. Subjects: consecutive patients admitted for rehabilitation to two general geriatric rehabilitation wards in each of two nearby district general hospitals. Methods: patients were assessed using standard tools (Barthel and Abbreviated Mental Test score) and various scales of the interRAI MDS assessment system (mental and physical functioning, pressure ulcers, continence, falls, mood), within a week of admission and up to one week before discharge. Place of residence prior to admission and discharge destination were determined. Results: on bivariate analysis there was a significant difference in discharge to residential and nursing homes between hospitals. Results from multivariate logistic regression analysis showed an increased risk for institutionalisation at discharge for women [odds ratio 2.42 (95% CI 1.41–4.14)] and patients with impaired cognitive function [odds ratio 1.53 (95% CI 1.28–1.82) for each point increase in MDS cognitive performance scale] and physical function [odds ratio 1.15 (95% CI 1.08–1.22) for each point increase in MDS short ADL scale]. Barthel and Abbreviated Mental Test showed similar odds ratios. Hospital did not remain a significant predictor of discharge destination following adjustment for patients' physical and cognitive function. Conclusions: comparisons of outcomes between hospitals could be misleading unless informed by standardised data on physical and mental functioning of rehabilitation patients.